Higher Efficiency and Temperature Reliability of Steam Generators at Thermal Power Stations - R. F. Kelbaliev; F. A. Ragimov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2010)
Methods for higher power unit efficiency and decrease of specific fuel consumption for electric-power generation have been considered in the paper. The paper reveals that a heat exchange intensification makes a positive effect on efficiency and temperature reliability of power engineering equipment while using coil and artificially turbulized (contoured) pipes. Results of experimental investigations on metal temperature at various mode parameters are proposed in the paper. The paper contains equations for determination of conditions initiating heat-transfer drop.